RESEARCH OF FACTORS AFFECTING THE IMPROVEMENT OF THE TRANSPORTATION SYSTEM IN THE REGION (Marketing Journal, 2025)
The article examines the factors influencing the improvement of the transport system of the Khorezm region. The level of influence of the transport system on the socio -economic development of the region is studied, and scientific proposals and recommendati ons for the development of transport services in the region are developed.
Keywords: transport; transport system; transport infrastructure; auto transport services